A Study Of Performance Appraisal Acceptance Among Employees The Manufacturing And Service Industries In Melaka - Sew, Ng Kwee (2000)
The aim of the study is to identify the factors that contribute to the acceptance of performance appraisal among employees in the manufacturing and service industry in Melaka.